2011
DOI: 10.1093/imanum/drr042
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation-collocation variational integrators

Abstract: We introduce a novel technique for constructing higher-order variational integrators for Hamiltonian systems of ordinary differential equations. In the construction of the discrete Lagrangian we adopt Hermite interpolation polynomials and the Euler-Maclaurin quadrature formula and apply collocation to the Euler-Lagrange equation and its prolongation. Considerable attention is devoted to the order analysis of the resulting variational integrators in terms of approximation properties of the Hermite polynomials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…www.zamm-journal.org Recently, Leok and Shingel [50] have proposed a variational integrator based on Hermite finite elements in time. Their formulation is derived from a prolongation-collocation approach: In addition to the discrete Euler-Lagrange equations this method accounts for the system's equation of motion in strong form,…”
Section: Relation To Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…www.zamm-journal.org Recently, Leok and Shingel [50] have proposed a variational integrator based on Hermite finite elements in time. Their formulation is derived from a prolongation-collocation approach: In addition to the discrete Euler-Lagrange equations this method accounts for the system's equation of motion in strong form,…”
Section: Relation To Other Methodsmentioning
confidence: 99%
“…Recently, Leok and Shingel have proposed a variational integrator based on Hermite finite elements in time. Their formulation is derived from a prolongation‐collocation approach: In addition to the discrete Euler‐Lagrange equations this method accounts for the system's equation of motion in strong form, mtrueẍtfalse(tfalse)+fxt(t)=0,{n,n+1}.For cubic Hermite shape functions — as they are used in our schemes — the velocities, boldv̂n and boldv̂n+1, are computed from Eq.…”
Section: Temporal Discretizationmentioning
confidence: 99%
“…Spectral variational integrators are described in (Hall and Leok 2014a) and prolongation-collocation methods in (Leok and Shingel 2012b).…”
Section: Variational Integrationmentioning
confidence: 99%
“…It can be shown that the midpoint approximation is a second order method with an error of the order O(h 2+1 ), see Marsden and West (2001, p. 402). The use of more sophisticated approximation schemes than (2.4) can however provide approximations of the exact flow of arbitrarily high order (see, e.g., Hairer, Lubich, & Wanner, 2005;Leokand & Shingel, 2011).…”
Section: The Variational Integrators Approach To Discretizationmentioning
confidence: 99%